MENINGKATKAN PERTUMBUHAN TANAMAN TOMAT (Lycopersicon esculentum) DENGAN SISTEM BUDIDAYA HIDROPONIK - Catur Wasonowati (Agrovigor, 2011)
Tomato is vegetable that has high economic and nutritional value. Hydroponics is the cultivation of plants without soil but using rice husk charcoal, rockwool, pumice, sand, gravel, perlite water and air media. This research aims to study the effect of nutrients and polybag size on growth and yield of hydroponic tomatoes. The experiment was conducted in Kassa House of Agroekoteknologi Departement Faculty of Agriculture Trunojoyo University. Fertilizers used were Hidrogroup and Greentonik while polybag size are 30x30 cm, 30x40 cm and 40x40 cm. The design of this study using Complete Randomized Design (CRD) with 3 replications. The result showed that this research affect to the vegetative phase. No interaction between type of nutrition and polybag size on plant height, leaf number, stem diameter, number of flowers, flowering time of tomato. Type of nutrition significantly affect plant height, leaf number, stem diameter, flower number and wet and dry weight of stems and leaves, whereas the size of polybags significantly affects in the number of leaves, wet and dry weight of stems and leaves of tomato.